2017
DOI: 10.5433/1679-0359.2017v38n2p981
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and chemical dehydration for pre-drying of black oat silage

Abstract: This study aimed to evaluate mechanical and chemical methods of forage dehydration in the production of black oat pre-dried silage (Avena strigosa Schreb) under different dehydration times. The experiment was conducted in a randomized block experimental design with five replications and arranged in a 2 x 6 factorial scheme. We assessed two methods of dehydration, mechanical and chemical, over six dewatering times, being made at 0, 3, 6, 9, 12, and 15 days after cutting or application of glyphosate. Harvest too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 13 publications
1
5
1
Order By: Relevance
“…The early cut ensured a good quality BOS, similar to reports by Carneiro et al (2017) from black oat silage (although pre-wilted) who also observed higher NDF content than in our experiment, but similar ADF content. evaluated black oat silage in micro-silos over different storage times, and found higher NDF and ADF, and lower CP content than results herein reported.…”
Section: Black Oat and Pasture Variablessupporting
confidence: 91%
See 1 more Smart Citation
“…The early cut ensured a good quality BOS, similar to reports by Carneiro et al (2017) from black oat silage (although pre-wilted) who also observed higher NDF content than in our experiment, but similar ADF content. evaluated black oat silage in micro-silos over different storage times, and found higher NDF and ADF, and lower CP content than results herein reported.…”
Section: Black Oat and Pasture Variablessupporting
confidence: 91%
“…The pH value of 4.2 in this work is below that reported by Carneiro et al (2017), who evaluated the effect of two pre-drying methods for black oat silage reporting pH values of 4.3 for the chemical method, and 4.7 for the mechanical method. On the other hand, Paris et al (2015) reported a lower pH value (3.9) for black oat silage in full flowering, after storage for 5 mo.…”
Section: Black Oat and Pasture Variablescontrasting
confidence: 57%
“…However, when glyphosate was applied at 500 mL ha -1 , 750 mL ha -1 , and 1000 mL ha -1 , DM contents were higher than control. Chemical desiccation prior to ensiling normally increases DM content because glyphosate affects stomatal conductance, cellular membrane selective permeability, and aquaporin functionality, thus reducing water absorption by plants (Zobiole et al, 2010;Carneiro et al, 2017;Bueno et al, 2018). Nevertheless, glyphosate doses above 1000 mL ha -1 may induce stomatal closure, which could reduce transpiration and carbon dioxide assimilation, decreasing the DM accumulation by plants (Brecke & Duke, 1980;Yannicari, Tambussi, Istilart, & Castro, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…This practice can generate high contamination with microorganisms undesirable to the fermentation, present in the soil, which, together with minerals in the soil, can contribute to haylage buffering (Horst et al, 2018). Therefore, some authors have instigated the use of other forage dehydration methods for harvesting and producing haylage, such as chemical dehydration using glyphosate (Carneiro et al, 2017;Bueno et al, 2018). Glyphosate inhibits the enzyme 5-enolpyruvylshikimate-3-phosphate-(EPSP) synthase, responsible for catalyzing the synthesis of shikimic acid, which acts in the conversion of carbohydrates derived from glycolysis and the pentose-phosphate route into aromatic amino acids (phenylalanine, tyrosine and tryptophan), which are precursors of lignin, alkaloids, flavonoids and benzoic acids, in addition to being important for protein synthesis and cell division in meristematic regions (Zobiole et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Acta Scientiarum. Animal Sciences, v. 45, e58323, 2023 Knowing that the dry matter content of the forage at the time of ensiling is a critical point to ensure adequate fermentation, and that although some authors have already suggested the appropriate times for this (Horst et al, 2017;Carneiro et al, 2017), the dehydration time necessary to reach such levels, as well as the alterations that each one generates in the digestibility of pre-dried silage are still rarely found in the literature. Thus, the objective was to evaluate the rate of in situ ruminal disappearance of dry matter and neutral detergent fiber from pre-dried black oat silage subjected to mechanical and chemical dehydration under six times of wilting in the field.…”
Section: Introductionmentioning
confidence: 99%